Myxomatous mitral valve disease in a Shih Tzu dog - Teoh, Y. B.; Khor, Kuan Hua (Veterinary Association Malaysia, 2017)
An 11-year-old intact male Shih Tzu dog was referred to the University Veterinary Hospital (UVH) with history of coughing and laboured breathing. Auscultation revealed that the dog had a left systolic heart murmur grade V/VI at the base of the heart. Radiography showed findings of cardiomegaly and pulmonary oedema. Echocardiography findings revealed that dog has a myxomatous mitral valve disease. The mitral valve was severely thickened and prolapsed into the left atrium. Congestive heart failure (CHF) was treated with an angiotensin converting enzyme (ACE) inhibitor and diuretic. An anti-mucolytic agent was prescribed as a symptomatic treatment for the coughing that could be due to mild bronchitis. Dog did not response well with treatment as the frequency of cough was not reduced and the duration was longer each time. Pimobendan was then added on to the initial treatment and there was a tremendous improvement seen from the patient after that. Episodes of productive cough were noticed greatly reduced and dog was much more active at home post two weeks of ACE inhibitor, diuretic and dual-acting inodilator. We successfully maintained the dog with minimal coughing episodes. However, the prognosis is moderate to poor in this case due to possibilities of refraction towards medications.